2019
DOI: 10.1080/09537287.2018.1501816
|View full text |Cite
|
Sign up to set email alerts
|

Integrating sustainable supply chain practices with operational performance: an exploratory study of Chinese SMEs

Abstract: In past few years, sustainable supply chain management practices have been getting increased attention in Chinese industries. With growing regulatory and market pressure to adopt green practices, SMEs are increasingly looking for innovative techniques to simultaneously improve the greenness of their processes while improving their operational performance. The paper aims to explore the green practices of Chinese SMEs in the packaging sector across different activities in its supply chain and understand the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 68 publications
3
60
1
2
Order By: Relevance
“…Unless practices such as the ISO 14000/14001 environmental management system, investment recovery, and eco-design are implemented, it is difficult to achieve environmental objectives (Miroshnychenko et al, 2017;Luthra et al, 2015), and hence the value of internal relational capital cannot be realized. Similarly, green purchasing and supplier management practices are essential for a manufacturer to benefit from supplier interaction and cooperation (Yu et al, 2017;Kumar et al, 2019). If a manufacturer does not use environmental criteria in supplier selection, evaluation, and auditing and in purchasing decisions, the supplier management interface developed through internal relational capital cannot improve inter-organizational processes (Zhu and Sarkis, 2007;Gopal and Thakkar, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unless practices such as the ISO 14000/14001 environmental management system, investment recovery, and eco-design are implemented, it is difficult to achieve environmental objectives (Miroshnychenko et al, 2017;Luthra et al, 2015), and hence the value of internal relational capital cannot be realized. Similarly, green purchasing and supplier management practices are essential for a manufacturer to benefit from supplier interaction and cooperation (Yu et al, 2017;Kumar et al, 2019). If a manufacturer does not use environmental criteria in supplier selection, evaluation, and auditing and in purchasing decisions, the supplier management interface developed through internal relational capital cannot improve inter-organizational processes (Zhu and Sarkis, 2007;Gopal and Thakkar, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, developing eco-friendly supply chains requires commitment and cooperation from supply chain partners (Zhu and Sarkis, 2007;Zhang et al, 2017;Zhu et al, 2013). Motivating suppliers and customers to collaborate and invest resources in green manufacturing has become a key challenge for manufacturers (Yu et al, 2014;Kumar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the uncertainty, a large number of studies pay attention to the sustainable supply chain network design due to the growing environmental impact, legislation and corporate social responsibility [ 24 , 25 , 26 , 27 ]. Jin et al [ 28 ] demonstrated that the sustainability requirement might reshape the optimal structure of a supply chain.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies instead emphasised the relationship between SSCM implementation and supply chain performance. Although still lacking a general consensus, many have recognised a positive relationship between SSCM practices and both environmental (Tappia et al 2015;Esfahbodi, Zhang, and Watson 2016;Kumar et al 2019) and financial performance (Golicic and Smith 2013;Savino, Manzini, and Mazza 2015;Gopal and Thakkar 2016b). With this in mind, other studies examined the barriers and drivers of implementing sustainable practices within a supply chain.…”
Section: Introductionmentioning
confidence: 99%